Developing English Reading Descriptive Text Materials Based on Scientific Approach for Grade X Students of Computer and Network Engineering Study Program at SMKS Harapan Al-Washliyah Sigambal - Aldino Syahreza Simatupang; Masitowarni Siregar (RIRAI Publisher, 2022)
The objective of this study was to develop materials of reading descriptive text as supporting learning for grade X computer and network engineering students at SMKS Harapan Al- Washliyah Sigambal. The research was conducted by using the simplication of Research and Development theory by Borg and Gall (2003) which simplified by Puslitjaknov (2008). The data was taken through observation, questionnaires, and interview. The materials were validated by an English lecturer and an English teacher by using validation sheets which is adapted from BSNP. The data were collected by using descriptive analysis and the materials were arranged based on Scientific Approach. The study’ results revealed that: (1) the materials used do not support the students study program because the topics of the materials are still considered general, (2) relevant reading materials are needed by students in vocational school especially in computer and network engineering study program, (3) the developed reading materials based on Scientific Approach have been validated with the score 3.52 from the first expert and 3.65 from the second expert which is in the range of 3.25 < ≤̅ 4.00 and categorized as “Very Good”. The reading descriptive text materials have been developed in accordance to the students’ needs based on Scientific Approach.